Coleoptera associated with Annonaceae in a Central Brazilian Cerrado - Saravy, Fábio Pinheiro (2021)
Knowledge on the interactions between insects and angiosperms is essential for the comprehension of the mechanisms that gave origin to the current biological diversity in terrestrial environments. These interactions are ancient, dating back, in conservative estimates, to Early Cretaceous, and being maintained through time in complex and interdependent associations. Pollination, one such example, connects the life histories of over one million organisms, and it is an important association, either on an ecological perspective as on an economic one. In other times considered occasional pollinators of a few plant species, the Coleoptera are nowadays viewed as efficient pollinators of plant species from many families, such as Arecaceae (palms), Nymphaeaceae (water lilies), Araceae and Annonaceae. The latter includes several plants of economic relevance worldwide, like the sugar apple, the soursop and atemoya. Cantharophilous Annonaceae flowers, i.e., pollinated by beetles, frequently delimit spaces more or less isolated from the exterior environment, referred to as floral chambers. There are basically two types of floral chambers in Annonaceae: small chambers, pollinated by small beetles which may have diurnal or nocturnal activity (Nitidulidae, Staphylinidae, small Curculionidae or Chrysomelidae), or larger floral chambers, visited by nocturnal beetles of the tribe Cyclocephalini (Scarabaeoidea, Melolonthidae). In the Cerrado, Annonaceae is represented by 75 species, some of which, like the araticum (Annona crassiflora Mart.), possess a poorly explored economic potential. Studies on Annonaceae pollination have been undertaken in the cerrados of Minas Gerais, São Paulo, Goiás, the Federal District and some municipalities in Mato Grosso. However, the unstudied Cerrado in the municipality of Chapada dos Guimarães, MT, where this study was accomplished, represents a disjunct area from the aforementioned, besides presenting climatic, edaphic and altitudinal specificities, which may influence on the taxonomic composition of the Annonaceae coleopteran floral visitors in the locality. The present study aims to analyze the interactions among beetles and three species of Annonaceae: Annona crassiflora, Xylopia aromatica (Lam.) Mart. and Cardiopetalum calophyllum Schltdl., the three of which occur sympatrically in the Cerrado Denso of Chapada dos Guimarães, MT. Although the three species bear flower chambers, A. crassiflora has a large floral chamber, whereas both X. aromatica and C. calophyllum possess small floral chambers. In the study area, which encompasses 76 hectares of Cerrado Denso, individuals of X. aromatica and C. calophyllum were sampled. In situ observations and records about the behavior of flower visitors of the three species were carried out. Flowers from such species were collected and taken to Laboratório de Ecologia e Taxonomia de Artrópodes (LETA) of the Instituto de Biociências da Universidade Federal do Mato Grosso for analyses to determine the presence of pollen load, cryptical behavioral aspects and morphospeciation of floral visitors. Observations and collections of strictly herbivorous Coleoptera in flowers and fruits of A. crassiflora were also accomplished. A review on the literature available on cantharophily in Cerrado plants is available in Chapter 1. The analysis of the flower visitors of X. aromatica, described in detail in Chapter 2, showed that it possesses a mixed pollination mode, involving insects of the order Thysanoptera and three morphospecies of Coleoptera: Cillaeus sp. 1 (Nitidulidae), Aleocharinae sp. 1 and Aleocharinae sp. 2 (Staphylinidae). Cillaeus and the two Staphylinidae species were relatively abundant in the floral chambers, and their behavior favors cross pollination in X. aromatica. Now C. calophyllum has been visited essentially by one Nitidulidae morphospecies, Lobiopa sp., whose presence in flowers both in female and male phase also favors cross pollination. The presence of Lobiopa sp. in 98,3% of the flowers, and of no other coleopteran visitor, shows that C. calophyllum holds a specialized interaction with this species. Furthermore, larvae of Lobiopa sp. also feed on the fallen corollas of C. calophyllum, which characterizes brood pollination. Such specialized mutualistic relationship is described in Chapter 3. A. crassiflora coleopteran floral visitors, described in Chapter 4, consisted in two species of Cyclocephalini: Cyclocephala celata and Cyclocephala quatuordecimpunctata. Two weevil species, Lydamis sp. 1 and Eurypages pennatus, are non-pollinating herbivores in, respectively, flowers and fruits of A. crassiflora. Only the latter has economic importance, because their larvae feed on seeds and pulp of this species’ fruits.